MEKHIMPAL MARRIAGE AND THE PROHIBITION OF SEPEKHINDING: AN EXAMINATION OF CUSTOMARY LAW AND ISLAMIC LAW IN THE MARRIAGE TRADITION OF THE ALAS COMMUNITY: KAWIN MEKHIMPAL DAN LARANGAN SEPEKHINDING: TELAAH HUKUM ADAT DAN HUKUM ISLAM DALAM TRADISI PERKAWINAN MASYARAKAT ALAS - Mohendra Rasyid; Dhiauddin Tanjung; Ramadhan Syahmedi Siregar (SOSIOEDUKASI, 2025)
This study, entitled “A Study on the Customary Prohibition of Cousin Marriage in the Alas Indigenous Community: Perspectives from Customary Law and Islamic Law,” aims to analyze the reasons behind the prohibition of cousin marriage in the Alas community, examine its compatibility with Islamic law, and explore its social implications within indigenous society. The research specifically investigates why marriages between paternal cousins (sepekhinding) and maternal cousins (pemekhenen) are prohibited, while marriages with the daughter of the father’s sister (mekhimpal) are encouraged under the customary concept of kawin mekhimpal. The study employs a qualitative field research method, with data collected from traditional elders and community leaders in Southeast Aceh through interviews and observation. Data were analyzed descriptively to interpret the relationship between customary norms and Islamic legal principles. The findings reveal that the prohibition of sepekhinding and pemekhenen marriages is rooted in the principle of preserving family honor, maintaining the integrity of the nuclear family, and preventing internal conflict within close kinship structures. Meanwhile, the encouragement of marriage with mekhimpal cousins symbolizes reciprocal relationships that strengthen social and familial cohesion in the extended family system. The results indicate that, based on the Qur’an, Hadith, and Islamic legal analogy (qiyās), the practice of cousin marriage itself is permissible in Islam. Therefore, the customary prohibition of marriage with certain cousins, such as sepekhinding and pemekhenen, is not aligned with Islamic law, which does not restrict marriage among cousins. The discussion highlights that the Alas customary system reflects a sociocultural adaptation aimed at maintaining harmony within the community, even though it differs from Islamic legal provisions. Hence, the study concludes that the customary practice has sociological and moral value but should be reinterpreted in light of Islamic jurisprudence to ensure alignment between religious law and local tradition.